SETTLEMENT OF CONSUMER DISPUTES THROUGH THE CONSUMER DISPUTE RESOLUTION AGENCY AND THEIR PROBLEMS - Dhaniswara K. Harjono; Hulman Panjaitan (Jurnal Hukum dan Peradilan, 2021)
In relation to fulfilling their daily needs, the position and existence of consumers in a dominant society are under businessmen. This has caused the potential loss of customers due to the actions of businessmen. It is not unusual for businessmen to exploit consumers for their interests and advantages without thinking and often neglecting the rights of consumers. This has given rise to disputes between consumers and businessmen that need to be resolved thoroughly and fairly, with legal certainty. The Act No. 8 of 1999 concerning consumer protection has regulated the resolution of consumer disputes which can be carried out outside the court through the Consumer Dispute Settlement Agency (BPSK). The existence of BPSK as a consumer dispute resolution institution does not seem to provide maximum protection to consumers because there are many problems, including the process and procedures for resolving disputes at BPSK. Based on the results of the research and analysis carried out, it is concluded that the resolution of consumer disputes through BPSK in terms of time is relatively faster because it has to be decided within a maximum of 21 working days compared to resolving consumer disputes through general courts which take years. But on the other hand, many problems exist related to the existence of BPSK as a consumer dispute resolution institution, including in the institutional sector, BPSK human resources, inconsistent laws, and so on.